2017
DOI: 10.1364/oe.25.010177
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz generation mechanism in nano-grating electrode photomixers on Fe-doped InGaAsP

Abstract: We report the generation mechanism associated with nano-grating electrode photomixers fabricated on Fe-doped InGaAsP substrates. Two different emitter designs incorporating nano-gratings coupled to the same broadband antenna were characterized in a continuous-wave terahertz (THz) frequency system employing telecommunications wavelength lasers for generation and coherent detection. The current-voltage characteristics and THz emission bandwidth of the emitters is compared for different bias polarities and optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this study, we demonstrated a THz detector by manipulating the nanoscale, ultrafast carrier dynamics through electric-field enhancement at the end of a nanoelectrode. Thus far, nano-electrodes have been adopted for the photonic THz devices [23][24][25] to utilize the plasmonic effect. In contrast, we showed the significance of the local field enhancement effect in nano-electrodes, apart from the plasmonic effect.…”
Section: Device Structure and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated a THz detector by manipulating the nanoscale, ultrafast carrier dynamics through electric-field enhancement at the end of a nanoelectrode. Thus far, nano-electrodes have been adopted for the photonic THz devices [23][24][25] to utilize the plasmonic effect. In contrast, we showed the significance of the local field enhancement effect in nano-electrodes, apart from the plasmonic effect.…”
Section: Device Structure and Fabricationmentioning
confidence: 99%
“…In recent studies on nano-electrode photoconductive THz devices [23][24][25], the significantly improved device performance has been partly attributed to the field-enhancement effect at the sharp end points of nano-electrodes, which locally improves the photocarrier collection. This suggests the possibility of manipulating the local carrier dynamics by changing the shape of the nanostructure.…”
Section: Introductionmentioning
confidence: 99%
“…They successfully enhanced photo-excitation of charge carriers through optical field concentration close to the electrodes [9][10][11][12][13][14][15][16][17] and through photon trapping. 18,19 However, the device architecture with plasmonic nanostructures often leads to reduced conductivity contrast between the OFF and ON states.…”
mentioning
confidence: 99%
“…In recent years, several groups have attempted to improve the conversion efficiency through the PC switch architecture, by integrating plasmonic nanostructures. They successfully enhanced photoexcitation of charge carriers through optical field concentration close to the electrodes and through photon trapping. , However, the device architecture with plasmonic nanostructures often leads to reduced conductivity contrast between the OFF and ON states. Furthermore, plasmonic nanostructures introduce significant Ohmic losses, limiting the conversion efficiency and leading to low device damage threshold.…”
mentioning
confidence: 99%